2019
DOI: 10.1007/s00894-019-3968-9
|View full text |Cite
|
Sign up to set email alerts
|

Motion in a crowded environment: the influence of obstacles’ size and shape and model of transport

Abstract: Simulations of motion in a complex crowded environment were performed. We employed the dynamic lattice liquid model, which was based on the cooperative movement concept. This algorithm is capable of working at very high densities, and the motion of all objects was highly correlated. The so-called motion of a single agent, where the motion of molecules is considered as a random walk without any correlation with other moving objects, was also calculated as the state of reference. Immobilized chains embedded in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
2
4
0
Order By: Relevance
“…The comparison of the total diffusion of HSs between I and N U phases showed that larger system densities hamper the tracers's diffusion at long timescales, similar to experimental results on the dynamics in crowded suspensions of spherical particles [55]. The occurrence of cage effects in crowded suspensions is related to the percolation of the systems [56], which depends not only on the system density, but also on the shape of the colloidal particles and, as a consequence, on their structural organisation. In systems of prolate HBPs, we observed larger deviations of the total NGP in I phases rather than in N U phases, even though I suspensions are less packed.…”
Section: Discussionsupporting
confidence: 79%
“…The comparison of the total diffusion of HSs between I and N U phases showed that larger system densities hamper the tracers's diffusion at long timescales, similar to experimental results on the dynamics in crowded suspensions of spherical particles [55]. The occurrence of cage effects in crowded suspensions is related to the percolation of the systems [56], which depends not only on the system density, but also on the shape of the colloidal particles and, as a consequence, on their structural organisation. In systems of prolate HBPs, we observed larger deviations of the total NGP in I phases rather than in N U phases, even though I suspensions are less packed.…”
Section: Discussionsupporting
confidence: 79%
“…At these times, the increased hydrogen bonding between water and CuB, as well as between water and the PCL chains (see Figure 3), contributes to the subdiffusive behavior of the water and CuB molecules. As expected, the MSDs for water are higher than those for CuB, which is mainly due to i) the relatively large molecular weight/size of the CuB molecules compared to the water molecules, making the CuB molecules more susceptible to diffusional hindrance in a crowded environment compared to the water molecules, [66][67][68] and ii) the fact that the majority of the water molecules are in the surrounding bulk solution, where they are undergoing diffusive Brownian motion. Overall, our observations are consistent with those of Mahdavi et al who studied the role of drug-water and water-nanocarrier hydrogen bonding on the diffusivity of the hydrophobic drug Doxorubicin in graphene oxide nanocarriers.…”
Section: Dynamical Properties Of the Cub-loaded Peo-b-pcl Micellesupporting
confidence: 55%
“…[63] (For the corresponding plots of MSD versus time, please see Figure S2, Supporting Information.) As can be seen, the plots exhibit multiple linear regimes with slopes of less than 1, reflecting the sub-diffusive motions of the CuB and water molecules caused by the presence of large multimolecular "obstacles" (or molecular crowding) [64][65][66] and hydrogen bonding. In the case of water, there are two linear regimes (defined approximately by t < 25 ps and t > 25 ps) up to log t ≈4.2 (i.e., ≈16 ns), the first having a lower slope than the second.…”
Section: Dynamical Properties Of the Cub-loaded Peo-b-pcl Micellementioning
confidence: 99%
“…Such behavior has been observed not only experimentally, for NPs in a polymer matrix, [129][130][131] but also from computer simulations, for polymers within porous 132 or confined media. 133 We can see in Fig. 9a that polymer and NP dynamics are similar at low NP volume fractions (f = 6.5% and 12%) for N = 200.…”
Section: Soft Mattermentioning
confidence: 79%